Multilayer all-solid-state composite positive electrode sheet and all-solid-state battery

By adopting gradient design and conductive agents with different specific surface areas in the composite positive electrode sheet of all solid state batteries, the problems of low conductivity and high resistance are solved, and the battery performance with high energy and power density is achieved.

CN118572027BActive Publication Date: 2024-12-31AESC DYNAMICS TECHNOLOGY (ORDOS) LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411052766.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-31
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

In all-solid state batteries, high energy and power density are hindered by low loading of positive active materials and insufficient effective ion conductivity, while high loading will lead to an increase in ion torsion and reduce battery performance.

Method used

The gradient design is adopted in an all-solid composite positive electrode sheet, and the proportion of solid electrolyte away from the positive electrode current collector side is increased, and the proportion of positive electrode active materials is increased on the positive electrode current collector side, and conductive agents with different specific surface areas are used to maximize the utilization of positive electrode active materials. and reduce the decomposition reaction of solid electrolytes.

Benefits of technology

It improves the effective ion conductivity and electron transmission performance of all solid-state batteries, achieves high power and energy density, and at the same time improves the capacity and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Embodiments of the present application provide a multilayer all-solid-state composite positive electrode sheet and an all-solid-state battery, wherein the multilayer all-solid-state composite positive electrode sheet comprises: a positive electrode current collector and three all-solid-state composite positive electrode layers arranged on the positive electrode current collector, wherein along the direction away from the positive electrode current collector, the three all-solid-state composite positive electrode layers are, in sequence, a first all-solid-state composite positive electrode layer, a second all-solid-state composite positive electrode layer and a third all-solid-state composite positive electrode layer, wherein each of the first to third all-solid-state composite positive electrode layers comprises a positive electrode active material, a solid electrolyte, a conductive agent and a binder, wherein, along the direction away from the positive electrode current collector and based on the mass of the corresponding all-solid-state composite positive electrode layer, the mass content of the positive electrode active material in the first to third all-solid-state composite positive electrode layers decreases in sequence, the mass content of the solid electrolyte increases in sequence, and the specific surface area of ​​the conductive agent decreases in sequence, thereby improving the effective ionic conductivity of the all-solid-state composite positive electrode sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and more specifically, to a multilayer all-solid-state composite positive electrode sheet and an all-solid-state battery. Background Art

[0002] In the rapid development of the new energy field, the development of lithium-ion batteries is particularly important, and all-solid-state batteries are regarded as one of the final forms of commercial lithium-ion batteries. By replacing flammable liquid electrolytes with solid electrolytes, users can be provided with safer next-generation power batteries with higher energy density and better long-term cycle performance. The energy and power density of all-solid-state batteries are largely determined by all-solid-state composite positive electrode sheets, which are mainly composed of positive electrode active materials and solid electrolytes. In order to achieve high energy and power density of all-solid-state batteries, the effective ionic conductivity of the solid electrolyte and the electronic conductivity of the positive electrode active materials in the all-solid-state composite positive electrode sheets must be high enough. In addition, achieving high energy density requires the use of thick positive electrodes and high positive electrode active material loading. However, increasing the proportion of positive electrode active materials in the all-solid-state composite positive electrode sheets will increase the ion tortuosity in the all-solid-state composite positive electrode sheets, thereby reducing the effective ionic conductivity of the all-solid-state composite positive electrode sheets. Low effective ionic conductivity will lead to low utilization of positive electrode active materials. So far, achieving high energy and power density in all-solid-state batteries has been hampered by low cathode active material loading and insufficient effective ionic conductivity of all-solid-state composite cathodes. Summary of the invention

[0003] In all-solid-state batteries, in order to achieve high battery capacity, the utilization rate of active materials in the all-solid-state composite positive electrode must be maximized. The applicant found that adding a conductive agent can improve its capacity and rate performance. However, different types of conductive agents have different specific surface areas. In descending order of specific surface area, the types of conductive agents are KB (~1300 m 2 / g)、CNT(~300 m 2 / g)、Super-P(~64 m 2 / g), VGCF (~24 m 2 / g). In addition, the effects of conductive agents with different specific surface areas on solid electrolytes vary greatly. As the specific surface area of ​​the conductive agent increases, the degradation trend of the solid electrolyte is stronger. The higher specific surface area of ​​the conductive agent corresponds to more reaction sites for the decomposition of the solid electrolyte. The decomposition of the solid electrolyte occurs at the interface between all conductive agents and the solid electrolyte. The formed products isolate the positive electrode active materials, thereby increasing the resistance of the all-solid-state composite positive electrode and reducing lithium ion transmission and battery performance. But at the same time, conductive agents with high specific surface areas can greatly improve the utilization rate of positive electrode active materials. Therefore, it is very important to make good use of conductive agents with different specific surface areas in the all-solid-state composite positive electrode plate. However, the prior art does not yet use conductive agents with different specific surface areas inside the all-solid-state composite positive electrode plate.

[0004] The present application improves the effective ionic conductivity of the all-solid composite positive electrode sheet by gradient design while maintaining a high positive electrode active material load, aiming to achieve high power and energy density. By increasing the proportion of solid electrolyte away from the positive electrode current collector side of the all-solid composite positive electrode sheet, ion transport in the all-solid composite positive electrode sheet can be enhanced. At the same time, increasing the proportion of positive electrode active material on the positive electrode current collector side ensures high positive electrode active material load and good electron transport.

[0005] In addition, the present application maximizes the utilization rate of the positive electrode active material by utilizing conductive agents with different specific surface areas while reducing the decomposition reaction of the conductive agent on the solid electrolyte, so as to improve the capacity and rate performance of the all-solid-state battery.

[0006] Some embodiments of the present application provide a multilayer all-solid-state composite positive electrode sheet, comprising: a positive electrode current collector and three all-solid-state composite positive electrode layers arranged on the positive electrode current collector, wherein along the direction away from the positive electrode current collector, the three all-solid-state composite positive electrode layers are successively a first all-solid-state composite positive electrode layer, a second all-solid-state composite positive electrode layer and a third all-solid-state composite positive electrode layer, wherein each of the first to third all-solid-state composite positive electrode layers comprises a positive electrode active material, a solid electrolyte, a conductive agent and a binder, wherein, along the direction away from the positive electrode current collector and based on the mass of the corresponding all-solid-state composite positive electrode layer, the mass content of the positive electrode active material in the first to third all-solid-state composite positive electrode layers decreases successively, the mass content of the solid electrolyte increases successively, and the specific surface area of ​​the conductive agent decreases successively.

[0007] The gradient design of the present application can improve the effective ionic conductivity of the all-solid-state composite positive electrode sheet while maintaining a high positive electrode active material load, aiming to achieve high power and energy density. By increasing the proportion of solid electrolyte away from the positive electrode current collector side in the all-solid-state composite positive electrode, ion transport in the all-solid-state composite positive electrode sheet can be enhanced. At the same time, increasing the proportion of positive electrode active materials on the positive electrode current collector side ensures high positive electrode active material load and good electron transport. In addition, while using conductive agents with different specific surface areas to maximize the utilization of positive electrode active materials, the decomposition reaction of the conductive agent to the solid electrolyte is reduced, thereby improving the capacity and rate performance of the all-solid-state battery.

[0008] In some embodiments, between two adjacent all-solid-state composite positive electrode layers of three all-solid-state composite positive electrode layers, based on the mass of the corresponding all-solid-state composite positive electrode layers, the mass content of the solid electrolyte in the all-solid-state composite positive electrode layer closer to the positive electrode current collector (i.e., before growth) is x1%, and the mass content of the solid electrolyte in the all-solid-state composite positive electrode layer farther away from the positive electrode current collector (i.e., after growth) is y1%, and x1 and y1 need to satisfy: -2≤x1+10-y1≤2.

[0009] In some embodiments, based on the mass of the corresponding all-solid composite positive electrode layer, the mass content of the solid electrolyte in the first all-solid composite positive electrode layer is 10% to 20%, the mass content of the solid electrolyte in the second all-solid composite positive electrode layer is 20% to 30%, and the mass content of the solid electrolyte in the third all-solid composite positive electrode layer is 30% to 40%. The content of the solid electrolyte is controlled by gradient design, and the proportion of the solid electrolyte away from the positive current collector side in the all-solid composite positive electrode plate is increased, and the proportion of the solid electrolyte within this range can maximize the enhancement of ion transport in the all-solid composite positive electrode plate.

[0010] In some embodiments, between two adjacent all-solid composite positive electrode layers of a plurality of all-solid composite positive electrode layers, based on the mass of the corresponding all-solid composite positive electrode layers, the mass content of the positive electrode active material in the all-solid composite positive electrode layer closer to the positive electrode current collector (i.e., before the reduction) is x2%, and the mass content of the positive electrode active material in the all-solid composite positive electrode layer farther away from the positive electrode current collector (i.e., after the reduction) is y2%, and x2 and y2 need to satisfy: -5≤x2-10-y2≤5. By gradient designing the mass content of the positive electrode active material, the proportion of the positive electrode active material on the positive electrode current collector side is increased, which can effectively improve the electron transport performance in the positive electrode active material layer.

[0011] In some embodiments, based on the mass of the corresponding all-solid composite positive electrode layer, the mass content of the positive electrode active material in the first all-solid composite positive electrode layer is 75% to 85%, the mass content of the positive electrode active material in the second all-solid composite positive electrode layer is 65% to 75%, and the mass content of the positive electrode active material in the third all-solid composite positive electrode layer is 55% to 65%. When the mass content of the positive electrode active material is within the above range, high positive electrode active material loading and good electron transport can be ensured to the greatest extent.

[0012] In some embodiments, the ratio of the mass content of the conductive agent in the first all-solid composite positive electrode layer, the second all-solid composite positive electrode layer, and the third all-solid composite positive electrode layer is 1:0.95-1.05:0.95-1.05. When conductive agents with different specific surface areas are used, the mass content of the conductive agent in the second all-solid composite positive electrode layer and the third all-solid composite positive electrode layer is adjusted within the above range, and the electrical performance of the all-solid-state battery is relatively stable.

[0013] In some embodiments, the specific surface area of ​​the conductive agent in the first all-solid composite positive electrode layer is 800 m 2 / g~1500 m 2 / g, the specific surface area of ​​the conductive agent in the second all-solid composite positive electrode layer is 200m 2 / g~300 m 2 / g, and the specific surface area of ​​the conductive agent in the third all-solid composite positive electrode layer is 13m 2 / g~25 m 2 / g. While using conductive agents with different specific surface areas to maximize the utilization rate of the positive electrode active material, the decomposition reaction of the conductive agent to the solid electrolyte is reduced. Specifically, by designing the specific surface area within the above range, the specific surface area of ​​the conductive agent in the first all-solid composite positive electrode layer is higher than 800m 2 / g~1500 m 2 / g, while the specific surface area of ​​the conductive agent in the third all-solid composite positive electrode layer is lower by 13m 2 / g~25 m 2 / g, which can maximize the capacity and rate performance of all-solid-state batteries.

[0014] In some embodiments, the total thickness of the positive electrode material layers including the three all-solid-state composite positive electrode layers is x3 μm, and the ratio of the specific surface area of ​​the conductive agent in the first all-solid-state composite positive electrode layer to the third all-solid-state composite positive electrode layer is y3 μm, then x3 and y3 need to satisfy: -1≤0.45x3-21-y3≤1.

[0015] In some embodiments, the solid electrolyte close to the positive electrode current collector is an oxide solid electrolyte, and the solid electrolyte away from the positive electrode current collector is a halide solid electrolyte or a sulfide solid electrolyte. In the present application, the use of an oxide electrolyte close to the positive electrode side can avoid side reactions caused by the conductive agent at the interface between the positive electrode and the electrolyte. At the same time, reducing the amount of oxide electrolyte and increasing the amount of sulfide solid electrolyte or halide solid electrolyte with high ionic conductivity can improve the overall ionic conductivity of the solid electrolyte layer.

[0016] In some embodiments, the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in each all-solid composite positive electrode is 55-85:10-40:1-3:0.5-2.

[0017] Other embodiments of the present application provide an all-solid-state battery, characterized in that it includes the above-mentioned multi-layer all-solid-state composite positive electrode sheet, negative electrode sheet and solid electrolyte layer.

[0018] In some embodiments, the solid electrolyte is a double-layer solid electrolyte, the solid electrolyte close to the multi-layer all-solid-state composite positive electrode plate is an oxide solid electrolyte, and the solid electrolyte close to the negative electrode plate is a halide solid electrolyte or a sulfide solid electrolyte, wherein the mass ratio of the solid electrolyte close to the multi-layer all-solid-state composite positive electrode plate to the solid electrolyte close to the negative electrode plate is 1~3:7~9.

[0019] The multi-layer all-solid-state composite positive electrode plate provided in the present application improves the capacity and rate performance of the corresponding all-solid-state battery. DETAILED DESCRIPTION

[0020] The following disclosure provides many different embodiments or examples for realizing the different features of the provided subject matter. Specific examples of components and arrangements are described below to simplify the present invention. Of course, these are merely examples and are not intended to limit the present invention. For example, in the following description, forming a first component above or on a second component may include an embodiment in which the first component and the second component are directly in contact with each other, and may also include an embodiment in which an additional component may be formed between the first component and the second component so that the first component and the second component may not be in direct contact. In addition, the present invention may repeat reference numerals and / or characters in various examples. This repetition is for the purpose of simplicity and clarity, and does not itself indicate the relationship between the various embodiments and / or configurations discussed.

[0021] Additionally, for ease of description, spatially relative terms such as "below," "beneath," "lower," "above," "upper," etc. may be used herein to describe the relationship of one illustrated element or component to another (or additional) element or component. Spatially relative terms are intended to encompass different orientations of the device in use or operation in addition to the orientation depicted. The device may be otherwise oriented (rotated 90 degrees or at other orientations) and the spatially relative descriptors used herein should likewise be interpreted accordingly.

[0022] In the field of new energy, the development of batteries is particularly important, and for the development of batteries, all-solid-state composite positive electrode sheets are becoming more and more important. The multilayer all-solid-state composite positive electrode sheet structure provided in the present application sets the content of positive electrode active materials to be higher near the positive electrode current collector and less in the area away from the positive electrode current collector, thereby solving the problems of high resistance generation and low capacity in previous all-solid-state batteries. The gradient design can improve the effective ionic conductivity of the multilayer all-solid-state composite positive electrode sheet while maintaining a high positive electrode active material load, aiming to achieve high power and energy density. By increasing the proportion of solid electrolytes away from the positive electrode current collector side in the multilayer all-solid-state composite positive electrode, ion transport in the all-solid-state composite positive electrode can be enhanced. At the same time, increasing the proportion of positive electrode active materials close to the positive electrode current collector ensures a high positive electrode active material load and good electron transport.

[0023] Specifically, the present application provides a multi-layer all-solid-state composite positive electrode sheet, comprising: a positive electrode current collector and three all-solid-state composite positive electrode layers arranged on the positive electrode current collector, wherein along the direction away from the positive electrode current collector, the three all-solid-state composite positive electrode layers are respectively a first all-solid-state composite positive electrode layer, a second all-solid-state composite positive electrode layer and a third all-solid-state composite positive electrode layer, wherein each of the first to third all-solid-state composite positive electrode layers comprises a positive electrode active material, a solid electrolyte, a conductive agent and a binder, wherein, based on the mass of the corresponding all-solid-state composite positive electrode layer, the mass content of the positive electrode active material in the first to third all-solid-state composite positive electrode layers decreases successively, the mass content of the solid electrolyte increases successively, and the specific surface area of ​​the conductive agent decreases successively.

[0024] In the present application, the multi-layer all-solid composite positive electrode sheet has a high ratio of positive electrode active materials, a low ratio of solid electrolytes, and a large specific surface area of ​​the conductive agent on the side close to the positive electrode current collector; and a low ratio of positive electrode active materials, a high ratio of solid electrolytes, and a small specific surface area of ​​the conductive agent on the side away from the positive electrode current collector. This multi-layer all-solid composite positive electrode sheet structural design can maximize the utilization of positive electrode active materials, while reducing the decomposition reaction of the conductive agent to the solid electrolyte, thereby improving the capacity and rate performance of the all-solid-state battery.

[0025] In some embodiments, between two adjacent all-solid-state composite positive electrode layers of the three all-solid-state composite positive electrode layers, based on the mass of the corresponding all-solid-state composite positive electrode layers, the mass content of the solid electrolyte in the all-solid-state composite positive electrode layer closer to the positive electrode current collector (i.e., before growth) is x1%, and the mass content of the solid electrolyte in the all-solid-state composite positive electrode layer farther away from the positive electrode current collector (i.e., after growth) is y1%, and x1 and y1 need to satisfy: -2≤x1+10-y1≤2. In some other embodiments, based on the mass of the corresponding all-solid-state composite positive electrode layer, the mass content of the solid electrolyte in the first all-solid-state composite positive electrode layer is 10%~20%, the mass content of the solid electrolyte in the second all-solid-state composite positive electrode layer is 20%~30%, and the mass content of the solid electrolyte in the third all-solid-state composite positive electrode layer is 30%~40%. In some embodiments, between two adjacent all-solid composite positive electrode layers of a plurality of all-solid composite positive electrode layers, based on the mass of the corresponding all-solid composite positive electrode layers, the mass content of the positive electrode active material in the all-solid composite positive electrode layer closer to the positive electrode current collector (i.e., before the reduction) is x2%, and the mass content of the positive electrode active material in the all-solid composite positive electrode layer farther away from the positive electrode current collector (i.e., after the reduction) is y2%, and x2 and y2 need to satisfy: -5≤x2-10-y2≤5. In addition, based on the mass of the corresponding all-solid composite positive electrode layer, the mass content of the positive electrode active material in the first all-solid composite positive electrode layer is 75%~85%, the mass content of the positive electrode active material in the second all-solid composite positive electrode layer is 65%~75%, and the mass content of the positive electrode active material in the third all-solid composite positive electrode layer is 55%~65%. In some other embodiments, the specific surface area of ​​the conductive agent in the first all-solid composite positive electrode layer is 800m 2 / g~1500 m 2 / g, and the specific surface area of ​​the conductive agent in the second all-solid composite positive electrode layer is 200m 2 / g~300 m 2 / g, and the specific surface area of ​​the conductive agent in the third all-solid composite positive electrode layer is 13m 2 / g~25 m 2 / g.

[0026] In the present application, the thicker the positive electrode material layer, the lower the utilization rate of the positive electrode active material close to the positive electrode current collector side. Therefore, using a conductive agent with a larger specific surface area on this side is beneficial to promoting the uniformity of the reaction kinetics in the depth direction of the positive electrode and improving the utilization rate of the positive electrode active material. When within the above range, the kinetic performance is optimal.

[0027] Furthermore, in the present application, for each of the first all-solid-state composite positive electrode layer, the second all-solid-state composite positive electrode layer and the third all-solid-state composite positive electrode layer, in the direction away from the positive electrode current collector, the mass content of the positive electrode active material inside the corresponding all-solid-state composite positive electrode layer tends to decrease successively, and the mass content of the solid electrolyte tends to increase successively.

[0028] In addition, for the multilayer all-solid composite positive electrode sheet provided in the present application, the ratio of the mass content of the conductive agent in the first all-solid composite positive electrode layer, the second all-solid composite positive electrode layer and the third all-solid composite positive electrode layer is: 1: (0.95-1.05): (0.95-1.05). In some embodiments, the total thickness of the positive electrode material layer including the three all-solid composite positive electrode layers is x3μm, and the ratio of the specific surface area of ​​the conductive agent in the first all-solid composite positive electrode layer to the third all-solid composite positive electrode layer is y3, then x3 and y3 need to satisfy: -1≤0.45x3-21-y3≤1. In some embodiments, the solid electrolyte close to the positive electrode current collector is an oxide solid electrolyte, and the solid electrolyte away from the positive electrode current collector is a halide solid electrolyte or a sulfide solid electrolyte. The solid electrolyte used on the inner edge of the multilayer all-solid composite positive electrode sheet of the present application close to the positive electrode current collector is an oxide solid electrolyte, and the solid electrolyte used on the side away from the positive electrode current collector is a halide solid electrolyte or a sulfide solid electrolyte. The inventors found in their research that the use of this design can avoid side reactions caused by the conductive agent at the interface between the positive electrode and the sulfide or halide electrolyte in the all-solid composite positive electrode close to the positive electrode current collector.

[0029] In the above embodiments, the binder includes one or more of polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer, polypropylene, polyethylene, ethylene-octene copolymer, polyimide, styrene-butadiene rubber, sodium alginate, polyacrylonitrile, polyurethane, polyacrylic acid, and polyvinylidene fluoride. In addition, the type of positive electrode active material is one or more of binary metal oxides, ternary metal oxides, and quaternary metal oxides. Further, the positive electrode active material includes one or more of lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), and lithium-rich manganese-based oxide (LRMO).

[0030] In the present application, the solid electrolyte includes but is not limited to one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte, and the type of the conductive agent is one or more of graphite, graphene, carbon black, carbon fiber and carbon nanotubes.

[0031] In some embodiments, the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent, and the binder in each all-solid composite positive electrode sheet is 55-85:10-40:1-3:0.5-2.

[0032] Other embodiments of the present application also provide an all-solid-state battery, which includes the above-mentioned multi-layer all-solid-state composite positive electrode plate, negative electrode plate and solid electrolyte layer.

[0033] In some embodiments, the solid electrolyte is a double-layer solid electrolyte, the solid electrolyte close to the multi-layer all-solid-state composite positive electrode plate is an oxide solid electrolyte, and the solid electrolyte close to the negative electrode plate is a halide solid electrolyte or a sulfide solid electrolyte, wherein the mass ratio of the solid electrolyte close to the multi-layer all-solid-state composite positive electrode plate to the solid electrolyte close to the negative electrode plate is 1~3:7~9.

[0034] In the present application, the use of oxide electrolytes near the positive electrode side can avoid side reactions caused by the conductive agent at the interface between the positive electrode and the electrolyte. At the same time, reducing the amount of oxide electrolytes and increasing the amount of sulfide solid electrolytes or halide solid electrolytes with high ionic conductivity can improve the overall ionic conductivity of the solid electrolyte layer.

[0035] Some other embodiments of the present application also provide a method for preparing the above-mentioned multi-layer all-solid composite positive electrode sheet, comprising the following steps:

[0036] S1. Weigh the positive electrode active material, solid electrolyte and conductive agent according to the rule that the proportion of positive electrode active material, solid electrolyte proportion and specific surface area of ​​conductive agent in the multi-layer all-solid composite positive electrode sheet decreases, increases and decreases in sequence from the side close to the positive electrode current collector to the side away from the positive electrode current collector (i.e., along the direction away from the positive electrode current collector).

[0037] S2. Mix the corresponding amount of positive electrode active material, solid electrolyte, conductive agent and fiberizable binder in a glove box to form a mixture. Then, the mixture is ball-milled to fiberize the binder to obtain a mass mixture. The mass mixture is repeatedly rolled at a corresponding temperature to a certain thickness to obtain different layers of all-solid composite positive electrode sheets;

[0038] S3. Roll-compress different layers of all-solid composite positive electrode sheets at a corresponding temperature to a certain thickness, and composite them with the positive electrode collector, and then hot-press them at a high temperature for a period of time to obtain the above-mentioned multi-layer all-solid composite positive electrode sheet.

[0039] Optionally, in the step S2, the rotation speed during ball milling is 100-1000 rpm, the mixing time is 0.5-3 h, the diameter of the ball milling zirconium beads is 5-20 mm, and the ball-to-material ratio is (20-50): 1. The applicant found in the research process that the above ball milling conditions can make the raw materials mixed more uniformly, thereby improving the interface compatibility between the components; at the same time, after high-energy ball milling, the heat generated makes the binder more easily fibrillated, and the fibrillated binder forms a three-dimensional cross-linked network inside the positive electrode to effectively fix the components.

[0040] Further optionally, the rotation speed of the ball milling mixing is 500 rpm, the ball milling time is 2 h, the diameter of the ball milling zirconium beads is 10 mm, and the ball-to-material ratio is 30:1.

[0041] The above rolling temperature is 60~120°C, and the rolling speed is 1~30 mm / s.

[0042] The positive electrode current collector is a carbon-coated aluminum foil with a thickness of 6-20 μm. The final multi-layer all-solid composite positive electrode sheet has a surface capacity of 1-10 mAh cm -2 .

[0043] The following takes all-solid-state lithium-ion battery as an example

[0044] All-solid composite positive electrode

[0045] The multilayer all-solid composite positive electrode sheet in the all-solid-state battery provided in the present application includes the above-mentioned positive current collector and the positive active material, solid electrolyte, conductive agent and binder arranged on the positive current collector. The positive active material can be one or more of binary metal oxides, ternary metal oxides and quaternary metal oxides. Further, the positive active material includes one or more of lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA) and lithium manganese-rich oxide (LRMO). The solid electrolyte is one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte, and the type of the conductive agent is one or more of graphite, graphene, carbon black, carbon fiber and carbon nanotubes. In addition, the binder is a fiberized binder, including one or more of polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer, polypropylene, polyethylene, ethylene-octene copolymer, polyimide, styrene-butadiene rubber, sodium alginate, polyacrylonitrile, polyurethane, polyacrylic acid, and polyvinylidene fluoride.

[0046] In addition, the positive electrode current collector may be a carbon-coated aluminum foil positive electrode current collector, however, other positive electrode current collectors commonly used in the art may be used.

[0047] Negative electrode

[0048] The negative electrode plate includes a negative electrode current collector and a negative electrode active material disposed on the negative electrode current collector. The negative electrode active material may be a graphite material, a silicon material, or a composite material composed of a combination of the two. In some embodiments, the graphite material may include but is not limited to natural graphite (block graphite, flake graphite, earthy graphite), artificial graphite (single crystal graphite, polycrystalline graphite, pyrolytic graphite, graphite fiber, etc.), etc.; the silicon material may include but is not limited to crystalline silicon, amorphous silicon, and organic silicon. In the negative electrode plate, the negative electrode current collector includes a copper current collector. In addition, in some other embodiments, the negative electrode active material may also be an alloy including indium, lithium, indium, aluminum, or at least two of the above metals.

[0049] Solid electrolyte layer

[0050] The solid electrolyte layer comprises solid electrolyte powder, and the solid electrolyte is one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.

[0051] The solid electrolyte layer is preferably a double-layer solid electrolyte, wherein the positive electrode side close to the multi-layer all-solid composite positive electrode plate can be selected as an oxide solid electrolyte, and the negative electrode side close to the negative electrode plate can be selected as a halide solid electrolyte or a sulfide solid electrolyte, wherein the mass ratio of the solid electrolyte close to the positive electrode side and the solid electrolyte close to the negative electrode side is 1~3:7~9.

[0052] The inventors found in their research that using oxide electrolytes near the positive electrode can avoid side reactions caused by the conductive agent at the interface between the positive electrode and the electrolyte. At the same time, reducing the amount of oxide electrolytes and increasing the amount of sulfide solid electrolytes or halide solid electrolytes with high ionic conductivity can improve the overall ionic conductivity of the solid electrolyte layer.

[0053] All-solid-state battery

[0054] The multi-layer all-solid composite positive electrode sheet, solid electrolyte layer and negative electrode sheet are sequentially placed into the mold for assembly; after assembly, pressurize and tighten the nut at the top of the column with a constant pressure to obtain an all-solid-state lithium-ion battery.

[0055] Note: The assembly process is completed in a glove box with an argon atmosphere, and the particle diameters of the corresponding powders of the all-solid-state composite positive electrode sheet, solid electrolyte layer and negative electrode sheet are kept consistent.

[0056] It should be noted that the all-solid-state battery prepared by the above method is an all-solid-state lithium-ion battery. However, the battery prepared in this application may also be an all-solid-state sodium-ion battery or a potassium-ion battery.

[0057] Those skilled in the art will understand that the above-described method for preparing the battery is only an example, and other methods commonly used in the art may be used without departing from the contents disclosed in the present application.

[0058] The reagents and raw materials used in the present invention are commercially available.

[0059] The present invention has no special requirements for the assembly method of the above-mentioned battery, and an assembly method familiar to those skilled in the art can be used. In addition, the above-mentioned technical solution can be applied not only to commonly used all-solid-state lithium-ion batteries, but also to all-solid-state sodium-ion batteries, all-solid-state potassium-ion batteries and other types of kinetic batteries.

[0060] Some specific embodiments and comparative examples are listed below to better illustrate the present application.

[0061] Example 1

[0062] Multi-layer all-solid composite positive electrode

[0063] The multi-layer all-solid composite positive electrode plate comprises a carbon-coated aluminum foil current collector, a first all-solid composite positive electrode layer, a second all-solid composite positive electrode layer and a third all-solid composite positive electrode layer, which are arranged in sequence from the side close to the current collector to the side far from the current collector.

[0064] The first all-solid composite positive electrode layer comprises a positive electrode active material, a solid electrolyte, a conductive agent and a binder; wherein the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder is 80:16:2:1.

[0065] The second all-solid composite positive electrode layer includes a positive electrode active material, a solid electrolyte, a conductive agent and a binder; wherein the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder is 70:26:2:1.

[0066] The third all-solid composite positive electrode layer includes a positive electrode active material, a solid electrolyte, a conductive agent and a binder; wherein the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder is 60:36:2:1.

[0067] The conductive agent in the first all-solid composite positive electrode layer is KB conductive agent with the highest specific surface area, which comes from Guangzhou Hengdeli New Energy Technology Co., Ltd., and the model is Ketjenblack EC 600 JD, with a specific surface area of ​​1270 m 2 / g.

[0068] The conductive agent in the second all-solid composite positive electrode layer is a CNT conductive agent with a relatively high specific surface area, which is from Dongguan Kelude New Energy Technology Co., Ltd., model CNT-3213, with a specific surface area of ​​280 m 2 / g.

[0069] The conductive agent in the third all-solid composite positive electrode layer is a VGCF conductive agent with a low specific surface area, which is from Showa Denko K.K., model VGCF-H, with a specific surface area of ​​27 m 2 / g.

[0070] The positive electrode active material is NCM, specifically LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0071] The solid electrolyte in the first all-solid composite positive electrode layer is an oxide solid electrolyte, specifically Li 6.5 LqCy 1.5 Ta 0.5 O 12 , from Shandong Chuanglu Advanced Battery Technology Co., Ltd., model LLZTO.

[0072] The solid electrolyte in the second all-solid-state composite positive electrode layer and the third all-solid-state composite positive electrode layer is a sulfide solid electrolyte, specifically Li6PS5Cl; it comes from Shandong Xinjieneng Lithium Battery Co., Ltd., and the model is LPSCl.

[0073] In the above-mentioned multi-layer all-solid-state composite positive electrode sheet, for the first all-solid-state composite positive electrode layer, the use of an oxide electrolyte can avoid the side reactions caused by the KB conductive agent with a high specific surface area. If a halide electrolyte or a sulfide electrolyte is used, the conductive agent with a high specific surface area will induce the decomposition of the solid electrolyte and hinder the ion transmission in the positive electrode material layer.

[0074] The binder is PTFE, which comes from Daikin Fluorochemical (China) Co., Ltd., model M-392.

[0075] The method for preparing the multi-layer all-solid composite positive electrode sheet comprises the following steps:

[0076] S1. Add the corresponding amount of LiNi 0.8 Co 0.1 Mn 0.1 O2、Li 6.5 LqCy 1.5 Ta 0.5 O 12 , KB conductive agent and PTFE are mixed in a glove box to form a mixture, and then the mixture is ball-milled to fiberize the binder to obtain a mass mixture, and the mass mixture is repeatedly rolled at 80° C. to a certain thickness to obtain a first all-solid composite positive electrode layer;

[0077] S2. Add the corresponding amount of LiNi 0.8 Co 0.1 Mn 0.1O2, Li6PS5Cl, CNT conductive agent and PTFE are mixed in a glove box to form a mixture, and then the mixture is ball-milled to fiberize the binder to obtain a mass mixture, and the mass mixture is repeatedly rolled at 80°C to a certain thickness to obtain a second all-solid composite positive electrode layer;

[0078] S3. Add the corresponding amount of LiNi 0.8 Co 0.1 Mn 0.1 O2, Li6PS5Cl, VGCF conductive agent and PTFE are mixed in a glove box to form a mixture, and then the mixture is ball-milled to fiberize the fiberized binder to obtain a mass mixture, and the mass mixture is repeatedly rolled at 80°C to a certain thickness to obtain a third all-solid composite positive electrode layer;

[0079] S4. Roll-compound the first all-solid composite positive electrode layer, the second all-solid composite positive electrode layer and the third all-solid composite positive electrode layer at 80 °C to a certain thickness, and then compound with carbon-coated aluminum foil. The thickness of the final multi-layer all-solid composite positive electrode sheet is 150 μm, and the surface capacity is 5 mAh cm -2 .

[0080] In the above preparation method, the thickness ratio of the first all-solid composite positive electrode layer, the second all-solid composite positive electrode layer and the third all-solid composite positive electrode layer is 1:1:1.

[0081] The ball milling speed was 500 rpm, the ball milling time was 2 h, the diameter of the zirconium beads was 10 mm, and the ball-to-material ratio was 30:1.

[0082] Negative electrode

[0083] The negative electrode sheet is a lithium-indium alloy sheet (the particle diameter of the corresponding negative electrode powder is φ=10 mm).

[0084] Solid electrolyte layer

[0085] The solid electrolyte layer consists of a first solid electrolyte layer close to the positive electrode side and a second solid electrolyte layer close to the negative electrode side. The first solid electrolyte layer is Li 6.5 LqCy 1.5 Ta 0.5 O 12 , and the second solid electrolyte layer is Li6PS5Cl, and the mass ratio of the first solid electrolyte layer to the second solid electrolyte layer is 2:8.

[0086] All-solid-state lithium-ion battery

[0087] S1. 100 mg Li 6.5 LqCy 1.5 Ta 0.5 O12 and 900 mg of Li6PS5Cl powder were placed in a mold with a diameter of 10 mm and pressurized to 100 MPa to obtain a solid electrolyte layer;

[0088] S2. Place the multi-layer all-solid-state composite positive electrode sheet and lithium-indium alloy sheet on both sides of the solid electrolyte layer in turn for assembly; after assembly, pressurize to 100 MPa and tighten the nut at the top of the column to maintain a constant pressure to obtain an all-solid-state lithium-ion battery.

[0089] Note: The assembly process was completed in a glove box with an argon atmosphere. The diameters of the multilayer all-solid composite positive electrode and the lithium-indium alloy sheet were both 10 mm.

[0090] Example 2

[0091] The preparation method is consistent with that of Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Example 2 is 80:16:1:1.

[0092] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 70:26:1:1.

[0093] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 60:36:1:1.

[0094] Example 3

[0095] The preparation method is consistent with that of Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Example 3 is 80:16:3:1.

[0096] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 70:26:3:1.

[0097] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 60:36:3:1.

[0098] Example 4

[0099] The preparation method is consistent with that of Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Example 4 is 75:16:2:1.

[0100] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 65:26:2:1.

[0101] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 55:36:2:1.

[0102] Example 5

[0103] The preparation method is consistent with that of Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Example 5 is 85:16:2:1.

[0104] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 75:26:2:1.

[0105] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 65:36:2:1.

[0106] Example 6

[0107] The preparation method is consistent with that of Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Example 6 is 80:10:2:1.

[0108] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 70:20:2:1.

[0109] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 60:30:2:1.

[0110] Example 7

[0111] The preparation method is consistent with that of Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Example 7 is 80:20:2:1.

[0112] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 70:30:2:1.

[0113] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 60:40:2:1.

[0114] Example 8

[0115] The preparation method is consistent with that of Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Example 8 is 82:18:2.5:0.5.

[0116] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 72:28:2.5:0.5.

[0117] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 62:38:2.5:0.5.

[0118] Example 9

[0119] The preparation method is consistent with that of Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Example 9 is 78:12:2:2.

[0120] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 68:22:2:2.

[0121] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 58:32:2:2.

[0122] Example 10

[0123] The preparation method is consistent with that of Example 1, except that the specific surface area of ​​the conductive agent in the first all-solid composite positive electrode layer in Example 10 is 800 m 2 / g.

[0124] The specific surface area of ​​the conductive agent in the second all-solid composite positive electrode layer is 200m 2 / g.

[0125] The specific surface area of ​​the conductive agent in the third all-solid composite positive electrode layer is 13m 2 / g.

[0126] Embodiment 11

[0127] The preparation method is consistent with that of Example 1, except that the specific surface area of ​​the conductive agent in the first all-solid composite positive electrode layer in Example 10 is 1000 m 2 / g.

[0128] The specific surface area of ​​the conductive agent in the second all-solid composite positive electrode layer is 260 m 2 / g.

[0129] The specific surface area of ​​the conductive agent in the third all-solid composite positive electrode layer is 18m 2 / g.

[0130] Example 12

[0131] The preparation method is consistent with that of Example 1, except that the specific surface area of ​​the conductive agent in the first all-solid composite positive electrode layer in Example 12 is 1500 m 2 / g.

[0132] The specific surface area of ​​the conductive agent in the second all-solid composite positive electrode layer is 300m 2 / g.

[0133] The specific surface area of ​​the conductive agent in the third all-solid composite positive electrode layer is 25m 2 / g.

[0134] Embodiment 13

[0135] The preparation method is consistent with that of Example 1, except that the mass ratio of the first solid electrolyte layer to the second solid electrolyte layer in the solid electrolyte layer in Example 13 is 1:7.

[0136] Embodiment 14

[0137] The preparation method is consistent with that of Example 1, except that the mass ratio of the first solid electrolyte layer to the second solid electrolyte layer in the solid electrolyte layer in Example 14 is 3:9.

[0138] Embodiment 15

[0139] The preparation method is consistent with that of Example 1, except that the positive electrode active material in Example 15 uses LNMO instead of LiNi 0.8 Co 0.1 Mn 0.1 O2, and the solid electrolyte uses Li3InCl6 to replace Li6PS5Cl.

[0140] The above LNMO is specifically LiNi 0.5 Mn 1.5 O4.

[0141] The above-mentioned Li3InCl6 comes from Guolian Automotive Power Battery Research Institute Co., Ltd., model HA01C.

[0142] Example 16

[0143] The preparation method is consistent with that of Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Example 16 is 80:16:1:1.

[0144] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 70:26:0.95:1.05.

[0145] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 60:36:0.95:1.05.

[0146] Embodiment 17

[0147] The preparation method is consistent with that of Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Example 17 is 80:16:1:1.

[0148] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 70:26:1.05:0.95.

[0149] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 60:36:1.05:0.95.

[0150] Comparative Example 1

[0151] The preparation method is consistent with that in Example 1, except that a single-layer all-solid composite positive electrode sheet is used in Comparative Example 1, wherein the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder is 80:16:3:1.

[0152] The conductive agent in the single-layer all-solid composite positive electrode is KB conductive agent with high specific surface area, which comes from Guangzhou Hengdeli New Energy Technology Co., Ltd. The model is Ketjenblack EC 600 JD, with a specific surface area of ​​1270 m 2 / g.

[0153] Comparative Example 2

[0154] The preparation method is consistent with that in Example 1, except that a single-layer all-solid composite positive electrode sheet is used in Comparative Example 2, wherein the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder is 60:36:3:1.

[0155] The conductive agent in the single-layer all-solid composite positive electrode is a VGCF conductive agent with a low specific surface area, which comes from Showa Denko K.K., model VGCF-H, with a specific surface area of ​​24 m 2 / g.

[0156] Comparative Example 3

[0157] The preparation method is consistent with that in Example 1, except that a single-layer all-solid composite positive electrode sheet is used in Comparative Example 3, wherein the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder is 60:36:3:1.

[0158] The conductive agent in the single-layer all-solid composite positive electrode is KB conductive agent with high specific surface area, which comes from Guangzhou Hengdeli New Energy Technology Co., Ltd. The model is Ketjenblack EC 600 JD, with a specific surface area of ​​1270 m 2 / g.

[0159] Comparative Example 4

[0160] The preparation method is consistent with that of Example 1, except that the conductive agent in the first all-solid composite positive electrode layer in Comparative Example 4 is a VGCF conductive agent with a low specific surface area, and the conductive agent in the third all-solid composite positive electrode layer is a KB conductive agent with a high specific surface area.

[0161] Comparative Example 5

[0162] The preparation method is consistent with that of Example 1, except that no conductive agent is added to the multi-layer all-solid composite positive electrode plate in Comparative Example 5.

[0163] Comparative Example 6

[0164] The preparation method is consistent with that in Example 1, except that the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid composite positive electrode layer in Comparative Example 6 is 80:16:5:1.

[0165] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid composite positive electrode layer is 70:26:5:1.

[0166] The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid composite positive electrode layer is 60:36:5:1.

[0167] Comparative Example 7

[0168] The preparation method is consistent with that in Example 1, except that the conductive agent in the first all-solid composite positive electrode layer, the second all-solid composite positive electrode layer and the third all-solid composite positive electrode layer in Comparative Example 7 is VGCF conductive agent with a low specific surface area.

[0169] Comparative Example 8

[0170] The preparation method is consistent with that in Example 1, except that the solid electrolyte in the first all-solid composite positive electrode layer, the second all-solid composite positive electrode layer and the third all-solid composite positive electrode layer in Comparative Example 8 is Li6PS5Cl.

[0171] Comparative Example 9

[0172] The preparation method is consistent with that in Example 1, except that the first solid electrolyte layer and the second solid electrolyte layer of the solid electrolyte layer in the all-solid-state lithium-ion battery in Comparative Example 9 are both Li6PS5Cl.

[0173] Comparative Example 10

[0174] The preparation method is consistent with that in Example 1, except that a single-layer all-solid composite positive electrode sheet is used in Comparative Example 10, and the positive electrode active material is replaced by LNMO. 0.8 Co 0.1 Mn 0.1 O2, and the solid electrolyte uses Li3InCl6 to replace Li6PS5Cl. The mass ratio of the positive electrode active material, solid electrolyte, conductive agent and binder is 80:16:3:1.

[0175] The above LNMO is specifically LiNi 0.5 Mn 1.5 O4. The above-mentioned Li3InCl6 comes from Guolian Automotive Power Battery Research Institute Co., Ltd., model HA01C.

[0176] The conductive agent in the single-layer all-solid composite positive electrode is KB conductive agent with high specific surface area, which comes from Guangzhou Hengdeli New Energy Technology Co., Ltd. The model is Ketjenblack EC 600 JD, with a specific surface area of ​​1270 m 2 / g.

[0177] Performance Testing Methods

[0178] Under 5 ℃ environment, the all-solid-state lithium-ion batteries prepared in Examples 1 to 17 and Comparative Examples 1 to 10 were charged and discharged for a long cycle after being fixed in capacity, and the number of cycles at room temperature was measured; the test conditions were that the battery was fixed in capacity and then a long cycle charge and discharge test was performed, and during the process, the first cycle fixed capacity discharge specific capacity and the number of cycles at room temperature when SOH was 80% were recorded; the operating voltage range was 1.9 to 3.7 V, the fixed capacity ratio was 0.1 C, and the normal temperature cycle test ratio was 0.3 C. For Example 4, its test method was the same as that of the other Examples and Comparative Examples, except that the operating voltage range was 1.4 to 4.25 V.

[0179] The test results are shown in Table 1 below.

[0180] Table 1. Performance test results of all-solid-state lithium-ion batteries of Examples 1 to 17 and Comparative Examples 1 to 10

[0181]

[0182]

[0183]

[0184] In combination with Examples 1 to 9 and Comparative Example 1, Example 15 and Comparative Example 10, it can be seen that when the proportion of positive electrode active materials, the proportion of solid electrolytes and the specific surface area of ​​the conductive agent in the multi-layer all-solid-state composite positive electrode sheet with a gradient design satisfy the corresponding relationship, that is, the mass content of the positive electrode active materials in the first all-solid-state composite positive electrode layer to the third all-solid-state composite positive electrode layer decreases successively, the mass content of the solid electrolyte increases successively, and the specific surface area of ​​the conductive agent decreases successively, the room temperature performance of the battery can be effectively improved.

[0185] When the mass content of the positive electrode active material in the first all-solid-state composite positive electrode layer in a single-layer all-solid-state composite positive electrode sheet is 75%~85%, the mass content of the positive electrode active material in the second all-solid-state composite positive electrode layer is 65%~75%, and the mass content of the positive electrode active material in the third all-solid-state composite positive electrode layer is 55%~65%, and between two adjacent all-solid-state composite positive electrode layers of a plurality of all-solid-state composite positive electrode layers, based on the mass of the corresponding all-solid-state composite positive electrode layers, the mass content of the positive electrode active material in the all-solid-state composite positive electrode layer closer to the positive electrode current collector (i.e., before reduction) is x2%, and the mass content of the positive electrode active material in the all-solid-state composite positive electrode layer farther away from the positive electrode current collector (i.e., after reduction) is y2%, and x2 and y2 satisfy: -5≤x2-10-y2≤5. By gradient designing the mass content of the positive electrode active material and making its mass content satisfy the above relationship, the proportion of the positive electrode active material on the positive electrode current collector side is increased, which can effectively improve the electron transport performance in the positive electrode active material layer and ensure high positive electrode active material loading and good electron transport to the greatest extent.

[0186] In addition, the mass content of the solid electrolyte in the first all-solid composite positive electrode layer is 10% to 20%, the mass content of the solid electrolyte in the second all-solid composite positive electrode layer is 20% to 30%, and the mass content of the solid electrolyte in the third all-solid composite positive electrode layer is 30% to 40%, and between two adjacent all-solid composite positive electrode layers of the three all-solid composite positive electrode layers, based on the mass of the corresponding all-solid composite positive electrode layers, the mass content of the solid electrolyte in the all-solid composite positive electrode layer closer to the positive electrode current collector (i.e., before growth) is x1%, and the mass content of the solid electrolyte in the all-solid composite positive electrode layer farther away from the positive electrode current collector (i.e., after growth) is y1%, and x1 and y1 satisfy: -2≤x1+10-y1≤2. By controlling the content of the solid electrolyte through gradient design, increasing the proportion of the solid electrolyte away from the positive electrode current collector side in the all-solid composite positive electrode sheet, and making the solid electrolyte content satisfy the above relationship, the ion transport in the all-solid composite positive electrode sheet can be enhanced to the greatest extent.

[0187] In addition, when the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder is 55~85:10~40:1~3:0.5~2, the content of the positive electrode active material is set to be higher near the positive electrode current collector and less in the area away from the positive electrode current collector, thereby solving the problems of high resistance generation and low capacity in previous all-solid-state batteries. In addition, within the above range, the gradient design can improve the effective ionic conductivity of the multilayer all-solid-state composite positive electrode sheet while maintaining a high positive electrode active material load, aiming to achieve high power and energy density. By increasing the proportion of solid electrolyte away from the positive electrode current collector side in the multilayer all-solid-state composite positive electrode, ion transport in the all-solid-state composite positive electrode can be enhanced. At the same time, increasing the proportion of positive electrode active materials close to the positive electrode current collector ensures a high positive electrode active material load and good electron transport.

[0188] In Comparative Example 1, when the mass ratio of the positive electrode active material, solid electrolyte, conductive agent and binder is 80:16:3:1, the energy density of the battery is high, but the proportion of solid electrolyte in the all-solid-state composite positive electrode plate is low, and a continuous ion transmission path cannot be established, so the battery performance deteriorates.

[0189] Further, as shown in the above embodiments 1-15, the total thickness of the positive electrode material layer including three all-solid composite positive electrode layers is x3μm, that is, 150μm, and the ratio of the specific surface area of ​​the conductive agent in the first all-solid composite positive electrode layer to the third all-solid composite positive electrode layer is y3, and x3 and y3 satisfy: -1≤0.45x3-21-y3≤1, and in combination with embodiments 10-12 and comparative examples 2-6, it can be seen that when a multi-layer all-solid composite positive electrode sheet with a gradient design is adopted, that is, the conductive agent in the first all-solid composite positive electrode layer has a specific surface area of ​​800m 2 / g~1500 m 2 The conductive agent with a high specific surface area in the range of 200 m / g is used, and the specific surface area of ​​the conductive agent in the second all-solid composite positive electrode layer is 200 m 2 / g~300 m 2 / g, and the conductive agent in the third all-solid composite positive electrode layer has a specific surface area of ​​13m 2 / g~25 m 2 / g range, in this case, the use of a conductive agent with a larger specific surface area close to the positive electrode current collector is conducive to promoting the uniformity of the reaction kinetics in the depth direction of the positive electrode and improving the utilization rate of the positive electrode active material. It can be seen that the present application uses conductive agents with different specific surface areas to maximize the utilization rate of the positive electrode active material while reducing the decomposition reaction of the conductive agent to the solid electrolyte, which can maximize the capacity and rate performance of the all-solid-state battery.

[0190] In Comparative Example 2, a single-layer all-solid composite positive electrode is used, and the mass ratio of the positive electrode active material, solid electrolyte, conductive agent and binder is 60:36:3:1, and the conductive agent in the all-solid composite positive electrode is a VGCF conductive agent with a low specific surface area. The energy density of the battery is low. Similarly, in Comparative Example 3, when a single-layer all-solid composite positive electrode is used, and the mass ratio of the positive electrode active material, solid electrolyte, conductive agent and binder is 60:36:3:1, and the conductive agent in the all-solid composite positive electrode is a KB conductive agent with a high specific surface area, the KB conductive agent with a high specific surface area will induce the decomposition of the solid electrolyte, isolate part of the ion path, and thus cause the battery performance to decline. This is because the gradient-designed multi-layer all-solid composite positive electrode effectively shortens the comprehensive ion diffusion distance in the electrochemical reaction process and promotes the electrode reaction kinetics, while the single-layer all-solid composite positive electrode does not have these advantages.

[0191] In addition, in Comparative Example 4, the conductive agent in the first all-solid-state composite positive electrode layer is a VGCF conductive agent with a low specific surface area, while the conductive agent in the third all-solid-state composite positive electrode layer is a KB conductive agent with a high specific surface area. At this time, the limited content of the low-surface-area VGCF conductive agent in the first all-solid-state composite positive electrode layer cannot fully utilize the positive electrode active material, and the high-specific-surface-area KB conductive agent in the third all-solid-state composite positive electrode layer will induce the decomposition of the solid electrolyte, isolating part of the ion path, thereby causing the battery performance to decline.

[0192] As further shown in Comparative Example 5, when a multi-layer all-solid-state composite positive electrode sheet with a gradient design is used but no conductive agent is added to the multi-layer all-solid-state composite positive electrode sheet, the battery performance deteriorates. This is because the electron transmission pathway of the all-solid-state composite positive electrode is blocked, and the electron transmission of the all-solid-state composite positive electrode requires the participation of the conductive agent.

[0193] In Comparative Example 6, although a gradient-designed multilayer all-solid-state composite positive electrode sheet is used, the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the first all-solid-state composite positive electrode layer is 80:16:5:1, the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the second all-solid-state composite positive electrode layer is 70:26:5:1, and the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in the third all-solid-state composite positive electrode layer is 60:36:5:1. It can be seen that the conductive agent exceeds the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in each all-solid-state composite positive electrode, which is 55~85:10~40:1~3:0.5~2, and the battery performance deteriorates. This is because the conductive agent content of the multilayer all-solid-state composite positive electrode sheet has a percolation threshold. After the conductive agent content reaches a certain value, further increasing the conductive agent content will not increase the electron transmission path, but will further induce the decomposition of the solid electrolyte, isolate part of the ion path, and thus cause the battery performance to deteriorate.

[0194] As further shown in Comparative Example 7, when the conductive agent in the first to third all-solid composite positive electrode layers is a VGCF conductive agent with a low specific surface area, the battery performance is reduced, because the utilization rate of the positive electrode active material close to the current collector side is affected. In addition, as shown in Comparative Examples 8 and 9, when the solid electrolyte in the first to third all-solid composite positive electrode layers is Li6PS5Cl, the battery performance is reduced, because the positive electrode and the sulfide or halide electrolyte interface in the positive electrode material layer close to the current collector side undergo a side reaction due to the conductive agent, which hinders the ion transport in the first all-solid composite positive electrode layer.

[0195] It can be seen from Examples 13-15 that the use of oxide electrolytes near the positive electrode side can avoid side reactions caused by the conductive agent at the interface between the positive electrode and the electrolyte. At the same time, the amount of oxide electrolytes is reduced, and the amount of sulfide solid electrolytes or halide solid electrolytes with high ionic conductivity is increased, so that the mass ratio of the solid electrolyte near the multi-layer all-solid composite positive electrode plate to the solid electrolyte near the negative electrode plate is 1-3:7-9, which can improve the overall ionic conductivity of the solid electrolyte layer.

[0196] It can be seen from Example 2 and Examples 16-17 that the ratio of the mass content of the conductive agent in the first all-solid composite positive electrode layer, the second all-solid composite positive electrode layer and the third all-solid composite positive electrode layer is: 1: 0.95-1.05: 0.95-1.05. When using conductive agents with different specific surface areas, the mass content of the conductive agent in the second all-solid composite positive electrode layer and the third all-solid composite positive electrode layer is adjusted within the above range, and the electrical performance of the all-solid-state battery is relatively stable.

[0197] The features of several embodiments are summarized above so that those skilled in the art can better understand various aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for performing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that such equivalent constructions do not deviate from the spirit and scope of the present invention, and that they can make various changes, substitutions and modifications herein without departing from the spirit and scope of the present invention.

Claims

1. A multi-layer all-solid composite positive electrode plate, characterized in that: include: A positive electrode current collector and three all-solid composite positive electrode layers arranged on the positive electrode current collector, wherein along the direction away from the positive electrode current collector, the three all-solid composite positive electrode layers are sequentially a first all-solid composite positive electrode layer, a second all-solid composite positive electrode layer and a third all-solid composite positive electrode layer, each of the first all-solid composite positive electrode layer to the third all-solid composite positive electrode layer comprises a positive electrode active material, a solid electrolyte, a conductive agent and a binder, Wherein, along the direction away from the positive electrode current collector and based on the mass of the corresponding all-solid composite positive electrode layer, the mass content of the positive electrode active material in the first all-solid composite positive electrode layer to the third all-solid composite positive electrode layer decreases successively, the mass content of the solid electrolyte increases successively, and the specific surface area of ​​the conductive agent decreases successively, The solid electrolyte close to the positive electrode current collector is an oxide solid electrolyte, and the solid electrolyte far from the positive electrode current collector is a halide solid electrolyte or a sulfide solid electrolyte.

2. The multi-layer all-solid composite positive electrode sheet according to claim 1, characterized in that: Between two adjacent all-solid-state composite positive electrode layers of the three all-solid-state composite positive electrode layers, based on the mass of the corresponding all-solid-state composite positive electrode layers, the mass content of the solid electrolyte in the all-solid-state composite positive electrode layer closer to the positive electrode current collector is x1%, and the mass content of the solid electrolyte in the all-solid-state composite positive electrode layer farther away from the positive electrode current collector is y1%, and x1 and y1 need to satisfy: -2≤x1+10-y1≤2.

3. The multi-layer all-solid composite positive electrode sheet according to claim 1, characterized in that: Based on the mass of the corresponding all-solid-state composite positive electrode layer, the mass content of the solid electrolyte in the first all-solid-state composite positive electrode layer is 10%~20%, the mass content of the solid electrolyte in the second all-solid-state composite positive electrode layer is 20%~30%, and the mass content of the solid electrolyte in the third all-solid-state composite positive electrode layer is 30%~40%.

4. The multi-layer all-solid composite positive electrode plate according to claim 1, characterized in that: Between two adjacent all-solid-state composite positive electrode layers of a plurality of all-solid-state composite positive electrode layers, based on the mass of the corresponding all-solid-state composite positive electrode layers, the mass content of the positive electrode active material in the all-solid-state composite positive electrode layer closer to the positive electrode current collector is x2%, and the mass content of the positive electrode active material in the all-solid-state composite positive electrode layer farther away from the positive electrode current collector is y2%, and x2 and y2 need to satisfy: -5≤x2-10-y2≤5.

5. The multi-layer all-solid composite positive electrode plate according to claim 1, characterized in that: Based on the mass of the corresponding all-solid-state composite positive electrode layer, the mass content of the positive electrode active material in the first all-solid-state composite positive electrode layer is 75%~85%, the mass content of the positive electrode active material in the second all-solid-state composite positive electrode layer is 65%~75%, and the mass content of the positive electrode active material in the third all-solid-state composite positive electrode layer is 55%~65%.

6. The multi-layer all-solid composite positive electrode plate according to claim 1, characterized in that: The ratio of the mass content of the conductive agent in the first all-solid composite positive electrode layer, the second all-solid composite positive electrode layer and the third all-solid composite positive electrode layer is 1:0.95-1.05:0.95-1.

05.

7. The multi-layer all-solid composite positive electrode plate according to claim 1, characterized in that: The specific surface area of ​​the conductive agent in the first all-solid composite positive electrode layer is 800 m 2 / g ~1500 m 2 / g, the specific surface area of ​​the conductive agent in the second all-solid composite positive electrode layer is 200 m 2 / g ~300 m 2 / g, and the specific surface area of ​​the conductive agent in the third all-solid composite positive electrode layer is 13 m 2 / g ~25 m 2 / g.

8. The multi-layer all-solid composite positive electrode plate according to claim 7, characterized in that: The total thickness of the positive electrode material layers including the three all-solid-state composite positive electrode layers is x3µm, and the ratio of the specific surface area of ​​the conductive agent in the first all-solid-state composite positive electrode layer to the third all-solid-state composite positive electrode layer is y3, then x3 and y3 need to satisfy: -1≤0.45x3-21-y3≤1.

9. The multi-layer all-solid composite positive electrode plate according to claim 1, characterized in that: The mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder in each all-solid composite positive electrode is 55-85:10-40:1-3:0.5-2.

10. An all-solid-state battery, characterized in that: It comprises a multi-layer all-solid composite positive electrode sheet, a negative electrode sheet and a solid electrolyte layer according to any one of claims 1 to 9.

11. The all-solid-state battery according to claim 10, characterized in that: The solid electrolyte is a double-layer solid electrolyte, the solid electrolyte close to the multi-layer all-solid-state composite positive electrode plate is an oxide solid electrolyte, and the solid electrolyte close to the negative electrode plate is a halide solid electrolyte or a sulfide solid electrolyte, wherein the mass ratio of the solid electrolyte close to the multi-layer all-solid-state composite positive electrode plate to the solid electrolyte close to the negative electrode plate is 1~3:7~9.